Distinct society: Cultural identity in twentieth-century Newfoundland literature - Fowler, Adrian (University of Ottawa (Canada), 2003)
This thesis examines selected representations of Newfoundland cultural identity in twentieth century Newfoundland literature from Norman Duncan, E. J. Pratt and George Allan England to Bernice Morgan, Patrick Kavanagh and Wayne Johnston. The discussion is located within a broad context of popular and scholarly writings on the subject and a conceptual framework influenced by Benedict Anderson's book Imagined Communities and Seamus Heaney's essay "The Sense of Place." Nineteenth century attempts to maintain the distinctiveness of Newfoundland identity were politically motivated by advocates of home rule, civil liberties and sovereignty, and constituted part of the rhetoric and mobilization that resulted in responsible government and dominion status for the colony. In the twentieth century, a variety of writers addressed the subject, some from the perspective of visitors, others from the perspective of residents. Early in the century, this resulted in representations in the heroic mode that focussed upon the struggle of outport Newfoundlanders to wrest a living from the sea. At mid-century, this myth of heroic Newfoundland was supplanted by the romantic myth of the old outport in which the community life of Newfoundland coastal villages was recorded and extolled. By the 1970s, the outports had become symbolic of Newfoundland but by this time they were also beset by enormous changes brought about by the Second World War, Confederation with Canada, and government policies of industrialization and resettlement. Some writers responded by intensifying explorations of the cultural roots of the province in the traditional life, others addressed the challenges of the present, which included issues of neo-colonialism and economic imperialism as well as cultural dislocation. In all of this, Newfoundland writers contributed in significant ways to the imagining of their community and the survival of a country of the mind.
Keywords: Literature, Modern.; Literature, Canadian (English).